Design of Induction Motor Drive Without Velocity Sensor Using Current Vector Controller with Full and Reduced Observer Moving to DQ Axis - Gunawan, Ridwan; Yusivar, Feri; Wahab, Wahidin; Kadir, Zuhal A. (UI Scholars Hub, 2006)
Design of Induction Motor Drive Without Velocity Sensor Using Current Vector Controller with Full and Reduced Observer Moving to DQ Axis. The observer is used in estimation velocity sensor usually in α-β axis, therefore this situation will need an extra transformation when we want to add compensator because the flux model is in direct and quadrature-axis dq. Every used the transformation to make possible emerge an error. So in this simulation is used a method to estimate the velocity of induction motor drive with observer that is moved to dq-axis. The model of actual motor used is in alfa-beta axis, but the observer use the motor models in rotor flux oriented control (RFOC).This matter, also to prove that the different models of motor drives can be used between the actual and estimated one. The simulation results with C-MEX S-function Matlab/Simulink 6.5 to show that the full order observer in dq axis gives better performance than the reduced order observer.